Lamb and mutton production in Kenya - Koning, R. de (Food and Agriculture Organization of the United Nations, 1976)
Breeding performance of Malawi Zebu kept under traditional management system was investigated. Reproductive data of 1500 cattle were analysed. Discussions and data on age at first calving, calving interval (CI), existence of a breeding season and also effects of month of calving on subsequent CI and effect of early weaning on CI in Malawi Zebu cows included.